Academic and behavioral interventions - Burns, Matthew K. (Guilford practical intervention in the schools series., 2012)
"This book addresses a crucial aspect of sustaining a response-to-intervention (RTI) framework in a school: selecting interventions with the greatest likelihood of success and implementing them with integrity. Leading RTI experts explain how to match interventions to students' proficiency levels, drawing on cutting-edge research about the stages of learning. Effective academic and behavioral interventions for all three tiers of RTI are described in step-by-step detail and illustrated with vivid case examples. In a large-size format with lay-flat binding for easy photocopying, the book features more than 40 reproducible planning tools and other helpful forms."-- Provided by publisher.